Human convalescent plasma protects K18-hACE2 mice against severe respiratory disease. (7th May 2021) - Golden, Joseph W.; Zeng, Xiankun; Cline, Curtis R.; Garrison, Aura R.; White, Lauren E.; Fitzpatrick, Collin J.; Kwilas, Steven A.; Bowling, Philip A.; Fiallos, Jimmy O.; Moore, Joshua L.; Sifford, Willie B.; Ricks, Keersten M.; et al.
Abstract : SARS-CoV-2 is the causative agent of COVID-19 and human infections have resulted in a global health emergency. Small animal models that reproduce key elements of SARS-CoV-2 human infections are needed to rigorously screen candidate drugs to mitigate severe disease and prevent the spread of SARS-CoV-2. We and others have reported that transgenic mice expressing the human angiotensin-converting enzyme 2 (hACE2) viral receptor under the control of the Keratin 18 (K18) promoter develop severe and lethal respiratory disease subsequent to SARS-CoV-2 intranasal challenge. Here we report that some infected mice that survive challenge have residual pulmonary damages and persistent brain infection on day 28 post-infection despite the presence of anti-SARS-COV-2 neutralizing antibodies. Because of the hypersensitivity of K18-hACE2 mice to SARS-CoV-2 and the propensity of virus to infect the brain, we sought to determine if anti-infective biologics could protect against disease in this model system. We demonstrate that anti-SARS-CoV-2 human convalescent plasma protects K18-hACE2 against severe disease. All control mice succumbed to disease by day 7; however, all treated mice survived infection without observable signs of disease. In marked contrast to control mice, viral antigen and lesions were reduced or absent from lungs and absent in brains of antibody-treated mice. Our findings support the use of K18-hACE2 mice for protective efficacy studies of anti-SARS-CoV-2 medical countermeasures (MCMs). They also support the use of this system to study SARS-CoV-2 persistence and host recovery.